Menjembatani merdeka belajar dengan nilai-nilai pendidikan Islam - Syafitri, Ruhul Zikraini; Azzahra, Qonita; Sari, Herlini Puspika (Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the integration of the Merdeka Belajar (MB) concept with Islamic educational values in order to form an education system that is adaptive to the times without losing its spiritual and moral foundations. The research approach used is library research by examining various journals, books, and scientific literature related to MB policies and Islamic educational principles. The results of the study show that both have the same orientation in shaping well-rounded individuals, intellectually intelligent, noble in character, independent, and socially responsible. This integration is evident in the flexible curriculum design, project-based learning methods, and authentic assessments that evaluate cognitive, affective, and spiritual aspects in a balanced manner. Teachers act as facilitators and role models of values, while schools function as spaces for Islamic character building. The conclusion of this study confirms that the synergy between Merdeka Belajar and Islamic values is a strategic step towards realizing meaningful, humanistic education that is strongly rooted in the values of monotheism and national character. Keywords: Integration, Independent Learning, Islamic Values, Character Education, Islamic Education